2020
DOI: 10.3390/ma13122710
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Different Bleaching Protocols, Used with and without Sodium Ascorbate, on Bond Strength between Composite and Enamel

Abstract: This in vitro study aims to evaluate whether a solution of 10% sodium ascorbate (SA) may exert a beneficial effect on the bonding of composite to enamel after using different bleaching agents and protocols. Microtensile bond strength (µTBS) was evaluated on 72 freshly extracted human central incisors, divided into eight experimental groups and one control group (total n = 9): Group 1 serves as control (nonbleached). Group 2 was bleached with 5% carbamide peroxide. Group 3 was bleached with 5% carbamide peroxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 34 publications
4
22
0
1
Order By: Relevance
“…In line with our study, de Oliveira et al ( 2011) stated that bleaching teeth releases significant amounts of oxygen 24 h after treatment [30]. Studies have also recommended postponing the bonding procedures when bleaching teeth until the remaining oxygen on the teeth surfaces can be removed [31,33,[35][36][37].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In line with our study, de Oliveira et al ( 2011) stated that bleaching teeth releases significant amounts of oxygen 24 h after treatment [30]. Studies have also recommended postponing the bonding procedures when bleaching teeth until the remaining oxygen on the teeth surfaces can be removed [31,33,[35][36][37].…”
Section: Discussionsupporting
confidence: 86%
“…This result is in line with the research conducted by Yusri et al (2016), who showed that sodium ascorbate 10% combined with Tween 80 0.2% has the lowest coronal microleakage after intra-coronal bleaching using 35% hydrogen peroxide and requires a minimum application time of 48 h before composite restorations [50]. Regardless of the peroxide residue, several studies have shown that short application times (2-10 min) for antioxidants can increase bond strength in restored teeth after bleaching, indicating that the short application of antioxidants can reduce free radicals that affect bleaching on dentin bonding [37,51,52]. However, the current study clearly showed a relationship between the duration of application of antioxidant materials and the reduction in dissolved oxygen; specifically, we showed that applying antioxidant materials for 48 h can minimize or even almost eliminate peroxide residues on teeth after bleaching.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, SA was used as a reference parameter because it is one of the most used AA 20 . In previous and current studies where this agent was used as a separate step before the adhesive procedure, SBS values were improved 27,55,[59][60][61] and even restored to the non-bleached control level 27,55 . A current study where 10% SA is used for 10 minutes as a previous step concludes that this AA significantly increases the bond strength.…”
Section: Discussionmentioning
confidence: 67%
“…A current study where 10% SA is used for 10 minutes as a previous step concludes that this AA significantly increases the bond strength. Only when it was applied following bleaching with 5% and 10% CP there was no significant difference in the µTBS values compared to the control group 61 . Unlike the latter, in this study sodium ascorbate was incorporated into the primer of the experimental adhesive system.…”
Section: Discussionmentioning
confidence: 75%
“…Several researchers reported that 10% SA is sufficient to reverse the reduction in bond strength for dentin and enamel after tooth whitening. 12,13,23,24 Therefore, 10% SA was preferred as an antioxidant in our study. In the recent study, the use of SA for equal of bleaching time was found to be sufficient to reverse the compromised bonding in the treated enamel.…”
Section: Discussionmentioning
confidence: 70%